2018
DOI: 10.1080/09614524.2018.1424802
|View full text |Cite
|
Sign up to set email alerts
|

Access to infrastructure and human well-being: evidence from rural Nepal

Abstract: This article documents the level of access to infrastructure and assesses its perceived impacts on human wellbeing in rural Nepal. It found more varied level of wellbeing in less remote communities and the perceived impacts of access to infrastructure on human wellbeing is higher in more remote areas. Notably, access to road received the highest priority among respondent followed by drinking water and irrigation. The methodology and findings of this study have practical implication for rural development in hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In Nepal, Jacoby (2000) and Fafchamps and Shilpi (2003) demonstrated that income, cropping intensity, access to non-farm employment, and education levels in rural areas progressively fall as travel times to markets increase. In a small-scale study of 3 Nepali village development committees, Sapkota (2018) found that households with longer travel times to services have higher poverty levels and lower levels of health, education, and reported happiness. Shrestha (2012) found that a 1% increase in travel times to paved roads decreased rural farmland values and implied profits by 0.25%.…”
Section: Development Roads and Accessibility In Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal, Jacoby (2000) and Fafchamps and Shilpi (2003) demonstrated that income, cropping intensity, access to non-farm employment, and education levels in rural areas progressively fall as travel times to markets increase. In a small-scale study of 3 Nepali village development committees, Sapkota (2018) found that households with longer travel times to services have higher poverty levels and lower levels of health, education, and reported happiness. Shrestha (2012) found that a 1% increase in travel times to paved roads decreased rural farmland values and implied profits by 0.25%.…”
Section: Development Roads and Accessibility In Rural Areasmentioning
confidence: 99%
“…As a result, Nepal's total road length has proliferated from a base of 2,700 km in the 1970s to over 80,000km in 2015; over 7,500km of new roads were built in 2017 and 2018 alone (World Bank, 2017;Ministry of Finance, 2015). Further propelling this spree are local political economies wherein every incentive aligns towards more road building: constituents routinely cite roads as the highest priority in meetings or surveys (Sapkota, 2018;World Bank, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The most common response for benefits of road improvement, easier to travel , is similar to responses from Indigenous people of Malaysia in support of roads (G. R. Clements et al., 2018). Satisfaction with travel is linked with subjective well-being (Ettema, Friman, Gärling, & Olsson, 2016; Sapkota, 2018), especially in poor remote areas. Local communities identified traffic accidents as a significant risk of road development, consistent with growing number of fatalities from road traffic accidents in Cambodia nationwide (Kitamura, Hayashi, & Yagi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In India each additional 10 km from a town is associated with a 3.2% reduction in mean earnings (Asher, S. et al 2016). In Nepal itself Sapkota (2017) finds that remote, rural villages have higher poverty levels and report lower levels of health, education and happiness after controlling for household fixed effects.…”
Section: Accessibility and Developmentmentioning
confidence: 99%